SIMULATION OF INITIAL STAGE OF STATIONARY FLAME FIRE IN INDOOR AREAS - V. V. Nevdakh; A. A. Antoshin; I. E. Zuikov (Наука и техника)
A computer simulation of the initial stage of stationary flame fire in an indoor area has been made with the help of FDS software (version 5). It has been shown that stationary and non-stationary heat release stages are present in a stationary fire according to mass burning rate. Duration of these stages depend on fire source intensity and its level. Non-stationary stage is characterized heat liberation pulsations which are irregular in amplitude and duration. The pulsations are caused by uprising of flame burning in the smoke scope.